Determinants of Place of Delivery Among Migrant Working Mothers in China - Guo C (International Journal of Women's Health, 2025)
Chunlan Guo1,2 1Department of Geography and Resource Management, The Chinese University of Hong Kong, Sha Tin, Hong Kong, People’s Republic of China; 2Shenzhen Research Institute, The Chinese University of Hong Kong, Shenzhen, People’s Republic of ChinaCorrespondence: Chunlan Guo, Email chunlanguo@outlook.com; chunlanguo@cuhk.edu.hkBackground: In China, there were about 78.0 million migrant working women, who moved for employment or business purposes. They generally face two main options for childbirth: delivering in their host communities or returning to their hometowns for childbirth. However, the national ratio between these two groups of migrant working mothers and the determinants influencing their place of delivery remain unknown.Methods: This study examined a sample of 16035 rural migrant working mothers from 31 province-level administrative units in China, using data from the China Migrant Dynamic Survey. These mothers all had at least one child under the age of 18 and had prior migration experience before becoming mothers. They were either employed or involved in business activities and had generated income for at least one month before the survey was conducted.Results: The results indicated that 49.6% migrant working mothers opted to give birth in host communities, while 50.4% returned to their hometowns for childbirth. Those working in the Northeastern region and other northern provinces like Ningxia and Inner Mongolia are more likely to give birth in host communities. In contrast, mothers working in economically developed regions such as Guangdong, Jiangsu and Zhejiang tend to return to their hometowns for childbirth. Several factors positively influence these decisions, including self-employment, postsecondary education, higher household income, having more children and longer migration. Conversely, higher individual income, the child’s age, inter-provincial migration and multiple migration experiences negatively impact the likelihood of giving birth in host communities.Conclusion: This study deepens the understanding of the childbirth strategies adopted by migrant working mothers and the interaction of migration and childbirth. It strives to offer valuable insights that could shape future policy studies and contribute to the creation of evidence-based recommendations. These recommendations could be instrumental for policymakers in addressing issues related to internal migration, migrant women and the overall wellbeing of migrant families.Keywords: internal migration, working mothers, migrant women, childbirth, place of delivery, spatial difference